A solitary mud-daubing wasp, Brachymenes dyscherus (Hymenoptera: Vespidae) fron Brazil with evidence of a life-cyde polyphenism - Camillo, Evandro (1999)
Nests ( n=60 ) of a solitary mud-daubing wasp, Brachymenes dyscherus were conected at Fazenda Santa Carlota, Cajuru, Sao Paulo, Brazil ín 1995 and 1996 . The multi-celled mud nests were constructed on the interior walls of abandoned houses in dry and shaded places. Nests were composed of 1 to 4 layers with cens constructed in two paralle! series. The number of cens per nest ranged from 3 to 62. Cells containing prey (larvae of Lepidoptera) numbered fram 4 to 29. B. dyscherus is a uniyoltíne species. Adults emerge from September to December, and nesting talces place at the beginning of the following year; however, the developmental period for some immatures with proloFlged diapause l3.Sted up to 596 days. The total duration of immature stages